Pengaruh pendidikan kesehatan terhadap pengetahuan dan sikap ibu tentang konsep halal dan sehat pada MPASI di wilayah puskesmas Bojongsari - Anggita Marti Meilany; Rakhmat Susilo (Jurnal Keperawatan Muhammadiyah, 2020)
THE EFFECTS OF HEALTH EDUCATION ON KNOWLEDGE AND ATTITUDE OF MOTHERS ABOUT HALAL AND HEALTHY CONCEPT ON COMPLEMENTARY FEEDING IN THE AREA OF PUSKESMAS (PUBLIC HEALTH CENTRE) BOJONGSARIBy Anggita Marti MeilanyUniversitas Muhammadiyah PurwokertoABSTRACTBackground: Complementary feeding is nutritious food and drinks given to babies or toddlers aged 6-24 months in order to fulfil the needs of nutrition besides breast milk. In Islam, halal and haram of food and drink product and also cosmetics are crucial issues and are seen as one of the core teachings of the religion. Thus, every Muslim, who will use or consume a product, is required by the religion to make sure whether the products are haram or halal.Objective: To identify the effects of health education on knowledge and attitude of housewife mother about the halal and healthy concept of complementary feeding. Method: The research is quantitative research using a quasi-experimental method with one group pre-test and post-test design. The research instrument is a questionnaire. A number of 44 respondents are taken as the research sample through total sampling. Result:There are effects of health education on knowledge and attitude of mother about the halal and healthy concept on complementary feeding in the area of Puskesmas Bojongsari with the significant p-value of 0.000 (0.05).Conclusion: Health education can be concluded to have effects on the change of knowledge and attitude of the mother.Keywords: halal, complementary feeding, knowledge, attitude.